Exploring Pre-Service English Teachers’ Beliefs About Their Digital Literacy Experiences in Teaching Practicum - Surya, Demas Bermani; Saefullah, Hilmansyah (Journal of Teaching of English, 2021)
This study described preservice teachers' beliefs about digital literacy experiences in their teaching practicum. The pre-service teachers’ beliefs were evaluated using Ajzen’s Theory of Planned Behavior (TPB), which explored pre-service teachers’ behavioral, normative, and control beliefs related to digital literacy experience in their teaching practicum and their relationship to their intentions to integrate digital literacy in their classrooms. This study was a narrative inquiry with four voluntarily participating pre-service English teachers as the participants who enrolled in Teaching Practicum program for approximately 6 months or 1 (one) semester in the classroom assisted by an in-service teacher during the global pandemic. Findings suggested that the beliefs of pre-service teachers of digital media & tools integration during teacher practicum were related to their behavioral beliefs about the benefits of digital literacy for promoting students’ 21st-century skills, assisting to maintain interest and preparation of students’ future; normative beliefs about meeting the expectations of school, students, mentor teacher and parents; and control beliefs saliently about the more of pre-service teachers’ professional preparation programs, technology, and curriculum as well as policy support. This study indicated a suggestion for the professional development programs to focus on the exposure, ability, and technological value of student teachers for their prospective classroom.